Évaluation des effets de quatre bio-insecticides (Azadiractine, Bacillus thuringiensis, Spinosad et Sincocine) sur Aphis gossypii (Homoptéra : Aphididés) et de ses ennemis naturels - CHAREF BENDAHA, Azzedine; DEBIANE, Abdelkader (My University, 2017)
Plant protection user chemical control, which remains the most appropriate mean in the fight against natural enemies, plants peppers infested with a Aphis gossypii are treted with four bio-insecticdes, Azadirachtine, B401, Spinosad and Sincocine with one dose homologue .The observation are realised on 7 dayes, pests ( the aphids) and four natural enemies of these pests which are beetles, hoverflies, parasitoïde, and midges in the adult level. The results revealed that three bio-insecticides (Azadirachtine ,Sincocine and spinosad) cause mortality,naturel enemies (labybirds and horverflies) are weakly sensitive to thres products ; however,parasitoide and midges are very sensitive Also the B401 have not any effect during the results.
Keywords: Aphis gossypii Bio-insecticide; Sincocine; Spinosad; Azadirachtine; B401; ladybugs; hoverflies; parasitoïde; Gall midge; ب 104; المن; المبيدات; سنكوسين; سبينوزا; ازايركتي; Syrphe; coccinelles; Cécidomyies; parasitoïdes